INTERNATIONAL CULTURAL FESTIVALS IN UZBEKISTAN: CULTURAL DIPLOMACY, HERITAGE PRESERVATION, AND CONTEMPORARY DEVELOPMENT - Teshaboyeva Nafisa Zubaydulla qizi,; Baratillayeva Ruxshona Faxriddin qizi, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract:  This  article  examines  the  development,  functions,  and  global significance of international cultural festivals held in Uzbekistan. It analyzes the role of  festivals  as  instruments  of  cultural  diplomacy,  heritage  preservation,  creative exchange,  and  socio-economic  growth.  Focusing  on  music  festivals,  film  forums, regional  celebrations,  and  traditional  events,  the  study  explores  how  Uzbekistan presents  its  cultural  identity  on  the  world  stage  while  fostering  intercultural communication.  The  article  also  reviews  contemporary  challenges  related  to sustainability, infrastructure, and heritage protection, and highlights opportunities for strengthening Uzbekistan’s cultural presence internationally.